2011
DOI: 10.1080/01431161.2010.532826
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the irrigated rice cropping patterns of the Mekong delta, Vietnam, through hyper-temporal SPOT NDVI image analysis

Abstract: Successful identification and mapping of different cropping patterns under cloudy conditions of a specific crop through remote sensing provides important baseline information for planning and monitoring. In Vietnam, this information is either missing or unavailable; several ongoing projects studying options with radar to avoid earth observation problems caused by the prevailing cloudy conditions have to date produced only partial successes. In this research, optical hyper-temporal Satellite Pour l'Observation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
129
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(131 citation statements)
references
References 28 publications
2
129
0
Order By: Relevance
“…We found good agreement in the spatial distribution of single, double and triple rice-cropping schemes compared to previous studies in the Mekong Delta that reported cropping scheme maps with accuracies similar to our product [6,8,49,66,77]. The major driving force behind a farmer's choice of cropping scheme is the availability and management of water [66].…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…We found good agreement in the spatial distribution of single, double and triple rice-cropping schemes compared to previous studies in the Mekong Delta that reported cropping scheme maps with accuracies similar to our product [6,8,49,66,77]. The major driving force behind a farmer's choice of cropping scheme is the availability and management of water [66].…”
Section: Discussionsupporting
confidence: 64%
“…We suspect that these dynamic changes are also one of the error sources contributing to the low producer accuracy of the single-cropped class compared to the 2005´2010 intersection. Single-cropped, rainfed rice is increasingly diminished in favor of more profitable shrimp and fish farming [8,66,78] and could thusly be misclassified when such a change occurred during our study period. In addition, this cropping scheme is less widely distributed and spatially homogeneous than double or triple crop rice and might therefore be underrepresented in the 2005 land-use map which is based on moderate resolution data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Satellite-based flood inundation maps can be a very important input for assessing the progression of floodwaters and the severity of the flood situation. In the past several years, many satellite techniques that use optical sensors have been proposed to detect flood inundation, including National Oceanic and Atmospheric Administration (NOAA)/advanced very high resolution radiometer (AVHRR) (Jain et al 2006), Landsat multispectral scanner system (MSS), thematic mapper (TM) (Hallberg et al 1973;Rango & Solomonson 1974), advanced land imager (ALI) (Amarnath 2013), Indian remote-sensing satellite (IRS) (Jain et al 2006), Satellite Pour l'Observation de la Terre (SPOT) VEGETATION (Nguyen et al 2012) and Terra MODIS (Xiao et al 2005;Sakamoto et al 2007). …”
Section: Introductionmentioning
confidence: 99%